2021
DOI: 10.1029/2020gc009536
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical Weakness of the Nankai Accretionary Prism: Insights From Vp Measurements of Drill Cuttings

Abstract: Knowledge of the stress state in subduction zones is crucial for understanding the mechanics of geological and geophysical processes occurring in subduction zones, such as earthquake generation (e.g., Moore & Saffer, 2001), stress changes during the earthquake cycle (e.g., Wang & Hu, 2006) and accretionary wedge formation (e.g., Dahlen, 1990). Rock strength, which must be known to determine the stress state, is often determined by combining a failure criterion with the relationship between P-wave velocity (V p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
9
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 47 publications
1
9
0
Order By: Relevance
“…Kitamura et al. (2021) also reported the porosity ‐ V p relationships consistent with the high‐ V p model of Erickson and Jarrard (1998) in the accretionary prism at Site C0002 based on laboratory measurements of cuttings samples. At Site C0009, porosity is almost constant throughout the entire depth range, whereas V p steeply increases at the boundary between the LKB and inner prism.…”
Section: Resultsmentioning
confidence: 53%
“…Kitamura et al. (2021) also reported the porosity ‐ V p relationships consistent with the high‐ V p model of Erickson and Jarrard (1998) in the accretionary prism at Site C0002 based on laboratory measurements of cuttings samples. At Site C0009, porosity is almost constant throughout the entire depth range, whereas V p steeply increases at the boundary between the LKB and inner prism.…”
Section: Resultsmentioning
confidence: 53%
“…The empirical models of Erickson and Jarrard (1998) (modified by Kitajima et al., 2017), Hoffman and Tobin (2004), and Kitamura et al. (2021) are also reported. A new inversion fit is also proposed (thick black line), based on Equation , with the coefficients of Table 1.…”
Section: Resultsmentioning
confidence: 97%
“…A third issue was the type of porosity considered. Initially, total porosity values were used (Hoffman & Tobin, 2004; Kitajima et al., 2017; Kitamura et al., 2021). Recent studies have shown that because of the effect of clay‐bound water on total porosity, better relationships with V p can be obtained using effective porosity (Jeppson & Kitajima, 2022; Tudge & Tobin, 2013).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations